Comprehensive study on dye sensitized solar cell in subsystem level to excel performance potential: A review. (15th September 2021) - Nandan Arka, Girija; Bhushan Prasad, Shashi; Singh, Subhash
Abstract: Solar cells are furthermost eminent alternative solar energy conversion devices and have great potential to conquer the energy needs of the society. In recent past, Dye sensitized solar cell (DSSC) has gained a significant research interest in research community owing to physically portable nature, simple fabrication process, customizable aesthetic look and reasonable efficiency. Regardless, it still struggles for the commercialization due to its low power conversion efficiency. Since significant dye anchoring site, light harvesting efficiency through plasmon effect and scattering effect, least undesired recombination of electrons, swift electrons transportation and greater catalytic activity etc. collectively accountable for the DSSC performance and hence the DSSC structure needs to comprehend in subsystem level (Substrate, transparent conductive oxide layer, blocking layer, semiconductive oxide layer, dye, electrolyte, counter electrode) in a single platform for the revival of cell potential. This review presented an exhaustive study on substrate, transparent conductive oxide layer, blocking layer, semiconductive oxide layer, dye, electrolyte and counter electrode respectively and addressed its development with insight discussion. Furthermore, the morphological change in semiconductive oxide layer, alteration in dye pigment based on green technology for significant light absorption and potential of liquid, quasi solid and solid states electrolyte for the revival is addressed. This review also facilitates with graphical contrast to understand and envision a direction towards determinant research scope.